Entrepreneurial Orientation as a Driver of Business Performance: Comparative Evidence from High-Tech and Traditional Start-Ups in Nepal - Shiwakoti, Samir; Timsina, Baburam; Subba, Binod Lingden (Journal of Business and Social Sciences Research, 2025)
This study compares the levels of entrepreneurial orientation (EO) between high-tech and traditional start-ups in Nepal, with particular attention to sectoral differences in innovativeness, proactiveness, risk-taking, autonomy, and competitive aggressiveness. Using a cross-sectional survey design complemented by a brief qualitative component, data were collected from 215 founders of high-tech and traditional start-ups through purposive sampling. An open-ended question captured founders’ perspectives on performance drivers, strategic decision-making, and sector-specific challenges. Quantitative data were analysed using statistical software, complemented by thematic analysis of qualitative responses to enhance the interpretation of sectoral differences. The findings indicate that high-tech start-ups exhibit significantly higher EO levels and stronger EO-performance relationships, with innovativeness, pro-activeness, and risk-taking emerging as the most influential predictors compared to traditional start-ups. Qualitative insights corroborate these results, showing that high-tech founders emphasis innovation, proactive opportunity recognition, and calculated risk-taking, whereas traditional entrepreneurs adopt more incremental and reactive strategies. The study highlights the need for sector-specific policies and capability-building initiatives to strengthen EO and enhance start-up performance in Nepal.